The Digital Catalyst for Sustainable Development in Europe: E-Government Perspective - Mempel-Śnieżyk, Anna; Hlaváček, Petr (Publishing House of Wroclaw University of Economics and Business, 2024)
The aim of the research was to assess the progress of e-government in EU countries and the extent to which it is linked to sustainable development. To this end, indices were used, namely the E-Government Development Index (EGDI) and Sustainable Development Goals (SDGs), to identify whether there are links between e-government development and sustainability. At the same time, the chapter highlights geographical links. Although the links between e-government development and sustainability development were identified in the chapter, there are differences in Europe, especially in northern and western countries compared to the group of south-eastern countries. It is also necessary to understand the underlying factors contributing to these disparities in order to ensure the balanced development of society, as well as from a sustainability perspective.
Mempel-Śnieżyk, A. & Hlaváček, P. (2024). The Digital Catalyst for Sustainable Development in Europe: E-Government Perspective. In B. Drelich-Skulska, M. Sobocińska, & A. Tomášková (Eds.), The Importance of Universities for Society and Economy. The Experience of Researchers from the Visegrád Group (pp. 111-124). Publishing House of Wroclaw University of Economics and Business.
Keywords: e-government; digitalisation; sustainable development; Sustainable Development Goals